Artificial Intelligence in Islamic Education - Nurul Islami; Fazal Akmal Musyarri (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
Abstrak This study aims to analyze theological studies and regulations regarding the use of artificial intelligence (AI) in Islamic education. There has been a rapid change in digitalization and a lack of regulation. The use of AI in Islamic education presents challenges, including the moral interaction between students and technology. This research uses a qualitative approach with a literature study method, and the data analysis technique is carried out using descriptive-analytical techniques, namely by critically reviewing the content of the literature to identify patterns of thought and comparing the concepts of theological studies with regulations on the use of artificial intelligence in Islamic education. The results of the study indicate that artificial intelligence can enhance personalized learning, administrative efficiency, and facilitate access to religious resources; however, it also raises theological issues regarding the validity of interpretations generated by algorithms, as well as the need for supervision by scholars in the chain of knowledge. Meanwhile, from the regulatory concept, there appears to be ambiguity in the existing norms; current regulations and circular letters from the ministry only provide limited protection and there are no specific rules for AI in the context of religious education. AI can be used as a tool to support the roles of clerics and teachers, not to replace them, and to provide suggestions. It is recommended that specific regulations, transparency in algorithms, data protection measures, and oversight by teachers be implemented. Kata Kunci : Kecerdasan Buatan, Pendidikan Islam, Regulasi